Enhancing problem-solving abilities through Geogebra-assisted discovery learning model for elementary school students - Afiana, Veny; Andrijati, Noening (Universitas Islam Negeri Raden Intan Lampung, 2024)
The students’ low problem-solving ability is due to a less meaningful learning process. This study aims to analyze the effect of applying the discovery learning model assisted by GeoGebra on the mathematical problem-solving abilities of fourth-grade elementary school students. This research employs the quasi-experimental design. The population of this study consisted of fourth-grade students at SDN Dabin III Pecangaan Jepara. The sample was taken using simple random sampling techniques. The data collecting technique used was a test. The data were analyzed using t-tests. The results of the data analysis showed that the average mathematics learning outcome of the experimental class was 81.03, which was higher than the control class (64.65). It can be concluded that using the discovery learning model with the assistance of GeoGebra significantly affects the problem-solving abilities of fourth-grade elementary school students. The implications of this research provide guidelines for curriculum innovation in facing future challenges.